A screening method to quantify the economic viability of off-grid in-stream tidal energy deployment. (October 2020) - Lafleur, Charlotte; Truelove, William AL.; Cousineau, Julien; Hiles, Clayton E.; Buckham, Bradley; Crawford, Curran
Abstract: This study provides a framework to assess the economic viability of introducing tidal energy in a remote community to be used as a rapid screening tool by communities or project developers. Tidal projects life-cycle costs are modelled using the capabilities of HOMER Pro. Communities are described by the local price of diesel fuel (as a metric of the cost of electricity), their electrical load scale, and the local tidal current resource. A sequence of HOMER Pro models, exploring a range of these parameters and tidal turbine rated power combinations, were performed in pursuit of a simple relationship with economic viability. A general structure emerged which suggested three conditions informing the economic viability of introducing tidal energy in a remote community. These conditions were found to also be useful for determining the economic "break-in" scale for a tidal stream turbine in a given remote community. As validation, a case study involving ten remote communities along the British Columbia coast was carried out using HOMER Pro. For all ten communities, the conditions either (a) predicted correctly that the community is not economically viable, or (b) predicted correctly that the community is economically viable and the minimum turbine scale. Highlights: An easily applied screening tool for tidal energy in off-grid communities is presented. Economic viability of tidal stream turbines in remote communities is characterized. Critical conditions for tidal resource, turbine capacity and fuel price are identified. The tool is validated as fast and accurate using 10 case study communities.